Be Your Own Guru: Personal And Business Enlightenment In Just 3 Days
Extensive research has proven that both personal and business success have more to do with emotional and spiritual intelligence than hard graft, perseverance or even good old common sense. The bad news is that no-one can \'give you\' either emotional or spiritual intelligence. But the good news is that - because those intelligences are already lying dormant deep within you - you can learn how to harness these powers for yourself. Effectively you\'ll become your own guru - and once you\'ve discovered how to tap into your hidden resources, you\'ll find yourself rapidly shortening the learning curve to both happiness and profits! Written in an engaging style by former journalist Olivia Stefanino, Be Your Own Guru is intriguing, inspiring and above all, accessible.